A fairy tale in the 5 kingdoms of living beings: theaching science in literacy (Research, Society and Development, 2020)
The relationship between science and art in teaching has enormous potential, which has been historically evidenced and has produced interesting results, such as those presented herein. Our science teaching activities focused on the theme of the five kingdoms of living beings in a class of the 1st year of Elementary School I, combining constructivist perspectives, meaningful learning and playful teaching. The interdisciplinary focus helped in the elaboration of a comic book, which allowed us to verify not only how the assimilation of the theme occurred, but also the promotion of both literacy and scientific education. The teaching methodology was carried out in stages and through qualitative research by participant observation. The proposed theme contributed surprisingly to the classes, as children felt rewarded for the interdisciplinary activities and we could observe that the inclusion of scientific themes for early age students, respecting the specificities of the age group, did not affect adversely their development, on the contrary, enhanced it.